2020
DOI: 10.3390/healthcare8040373
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Post-Traumatic Stress Disorder after Coronavirus Disease

Abstract: Background: The coronavirus disease (COVID-19) emerged from China and rapidly spread to many other countries. In this study, we investigated the prevalence of post-traumatic stress disorder (PTSD) among patients with COVID-19 who were treated and discharged from a university hospital in Daegu, Korea. Methods: In total, 64 patients who were diagnosed with COVID-19 and then hospitalized, treated and discharged from the university hospital between February and April 2020 participated in our study. We conducted te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
4
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 37 publications
10
57
4
10
Order By: Relevance
“…Our prevalence rates are in the lower range of the 7-34%, which was reported in other cohorts of COVID-19 survivors following hospitalization at comparable time points [6][7][8][18][19][20][21], and much lower than the 96% reported during hospitalization in a study using the PCL-C, a civilian version of a PTSD questionnaire based on DSM-IV [22]. Two of the studies also comprised both hospitalized and non-hospitalized subjects [7,21].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Our prevalence rates are in the lower range of the 7-34%, which was reported in other cohorts of COVID-19 survivors following hospitalization at comparable time points [6][7][8][18][19][20][21], and much lower than the 96% reported during hospitalization in a study using the PCL-C, a civilian version of a PTSD questionnaire based on DSM-IV [22]. Two of the studies also comprised both hospitalized and non-hospitalized subjects [7,21].…”
Section: Discussioncontrasting
confidence: 58%
“…The few follow-up studies of survivors 1-3 months after COVID-19 hospitalizations have reported significant PTSD symptoms among 12-22%, as measured by the PTSD symptom checklist for DSM 5 (PCL-5) [6][7][8]. Non-hospitalized subjects constitute a much larger patient group than those hospitalized, and to the best of our knowledge, no previous study has assessed PTSD symptoms several months after COVID-19 in a consecutive sample of both hospitalized and non-hospitalized patients in a population-based study.…”
Section: Introductionmentioning
confidence: 99%
“…Manifestations may include obsession and compulsion, reduced social activity, poor concentration, aggression, irritability, substance use, and cognitive deficit [ 37 ]. Post-traumatic stress disorder; a psychiatric condition induced by life-stressing factors, could occur after recovery from a life-threatening illness, including COVID-19; as shown by recent studies, the prevalence rate may range from 5.8% to 43% [ 25 , 41 , 42 , 43 ]. Neurological post-COVID complications have also been reported, including late-onset Guillain-Barré syndrome, opsoclonus-myoclonus syndrome, acute transverse myelitis.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…The duration of follow-up ranged from two weeks to 4 months post hospital discharge 56,61 (Table 1). Post-traumatic stress disorder (PTSD) is deemed one of the common psychological complications among COVID-19 survivors 15,16,58 . Two studies have evaluated the PTSD according to post-traumatic stress disorder checklist-5 (-5) 15,58 .…”
Section: Nervous System Sequelaementioning
confidence: 99%